Brand coolness in a competitive environment: An empirical study on starbucks Turkey - Akyüz, Ayşen; Pınarbaşı, Fatih (Springer, 2020)
Brand-consumer relationship is a major area of research for many years and many aspects of brand related concepts have been studied in different contexts. As being one of the fundamental brand phenomenons, brand personality has long been a question of interest among researchers. Brand coolness is a new topic in brand literature and a few studies have explored this concept empirically. In this exploratory study, the brand coolness of Starbucks, the significance levels related to frequency of coffee consumption and brand coolness’ characteristics and the relationship of brand coolness and attitude towards Starbucks Turkey are being explored. Three hundred and seven surveys, collected from university students between the dates of 17th and 20th of November, 2019, were taken into analysis. t-test and correlation analysis were conducted and findings have been indicated in the study.
Keywords: Brand Coolness; Brand Identity; Brand Personality; Starbucks